THE IMPACT OF TAX E-FILING SYSTEM QUALITY ON TAXPAYER SATISFACTION: PERCEIVED USEFULNESS AS MEDIATOR - Muslichah Muslichah; Mohamed Bashir; Tutik Arniati (JRAK, 2023)
Tax e-filing system quality is vital, directly shaping tax process efficiency and user convenience. This study aims to examine the effect of tax e-filing system quality on taxpayer satisfaction using perceived usefulness as a mediating variable. To gather data, 300 questionnaires were distributed to taxpayers, resulting in participation from 230 respondents.The findings of our study demonstrated a positive effect of tax e-filing system quality on both user satisfaction and perceived usefulness, and that perceived usefulness has a positively significant effect on user satisfaction. Furthermore, this study confirmed that perceived usefulness as a mediating variable in the e-filing system quality and user satisfaction relationship. The study enhances tax system theory by revealing the mediating role of perceived usefulness, and it practically suggests improving e-filing systems for increased taxpayer satisfaction and efficient tax collection.